SYSTEMATIC LITERATURE REVIEW : ANALISIS PENERAPAN MODEL PROJECT-BASED LEARNING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS DAN SELF-CONFIDENCE SISWA - Anggiana, Agus Dede; Suciawati, Vici; Rahman, Taufik (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2023)
The purpose of this study was to analyze the application of the project-based learning (PjBL) model to students' mathematical communication skills and self-confidence. The research method used is a systematic literature review (SLR), meaning that this research is the result of a systematic review of literature on related topics. A search for relevant articles was carried out in article published from 2016 to 2022 which examine project-based learning, mathematical communication and self-confidence. The literature review comes from online articles from Google Scholar and Mendeley. Based on the research results, there is a positive impact on the application of the project- based learning (PjBL) model on students' mathematical communication abilities and self- confidence. Among them are student-centered learning, learning becomes more meaningful, students can explore knowledge, relate to contextual problems, are active and enthusiastic in discussing